Real-Time Injection Pressure Sensing and Minimal Intensity Stimulation Combination During Ultrasound-Guided Peripheral Nerve Blocks: An Exploratory Observational Trial. (February 2021) - Varobieff, Maxime; Choquet, Olivier; Swisser, Fabien; Coudray, Adrien; Menace, Cecilia; Molinari, Nicolas; Bringuier, Sophie; Capdevila, Xavier
Abstract : BACKGROUND: Nerve damage can occur after peripheral nerve block (PNB). Ultrasound guidance does not eliminate the risk of intraneural injection or nerve injury. Combining nerve stimulation and injection pressure (IP) monitoring with ultrasound guidance has been suggested to optimize needle tip location in PNB. In this prospective observational study, we hypothesized that measured pairs of IP and minimum intensity of stimulation (MIS) might differentiate successive needle tip locations established by high-resolution ultrasound during PNB. METHODS: For this exploratory study, 240 observations for 40 ultrasound-guided PNBs were studied in 28 patients scheduled for orthopedic surgery. During the progression of the needle to the nerve observed by ultrasonography, the IP was measured continuously using a computerized pressure-sensing device with a low flow rate of solution. Stimulation thresholds and electrical impedance were obtained by an impedance analyzer coupled to the nerve stimulator at 6 successive needle positions. The median (quartile) or mean (95% confidence interval [CI]) was reported. A mixed model analysis was used, and the sample was also explored using a classification and regression tree (CART) algorithm. RESULTS: Specific combinations of IP and MIS were measured for subcutaneous, epimysium contact, intramuscular, nerve contact (231 mm Hg [203–259 mm Hg] and 1.70 mA [1.38–2.02 mA]), intraneural location (188 mm Hg [152–224 mm Hg] and 0.58 mA [0.46–0.70 mA]), and subparaneural location (47 mm Hg [41–53 mm Hg] and 1.35 mA [1.09–1.61 mA]). The CART algorithm shows that the optimal subparaneural needle tip position might be defined by the lowest pressure (<81.3 mm Hg) and MIS (<1.5 mA) cutoffs. CONCLUSIONS: Our exploratory study evaluated concepts to generate hypotheses. The combinations of IP and MIS might help the physician during a PNB procedure. A low IP and low MIS might confirm a subparaneural location, and a high IP and a low MIS might be an alert for the intraneural location of the needle tip.